2020
DOI: 10.3390/s20123381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cooled and Uncooled IR Sensors by Means of Signal-to-Noise Ratio for NDT Diagnostics of Aerospace Grade Composites

Abstract: This work aims to address the effectiveness and challenges of non-destructive testing (NDT) by active infrared thermography (IRT) for the inspection of aerospace-grade composite samples and seeks to compare uncooled and cooled thermal cameras using the signal-to-noise ratio (SNR) as a performance parameter. It focuses on locating impact damages and optimising the results using several signal processing techniques. The work successfully compares both types of cameras using seven different SNR definitions, to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Uncooled sensors, on the other hand, are smaller in both size and weight at the cost of inferior all-around performance. However, the study in [ 31 ], which compared a high-end cooled FLIR Phoenix to the more affordable uncooled system Variocam, showed that the uncooled thermal system could compensate for its lower resolution sensitivity via further image processing. Furthermore, the study also showed that the uncooled thermal sensor was still suitable for use in UAVs for navigation applications by analysing SNR data.…”
Section: Thermal Sensor System Considerations For Navigation Applicationsmentioning
confidence: 99%
“…Uncooled sensors, on the other hand, are smaller in both size and weight at the cost of inferior all-around performance. However, the study in [ 31 ], which compared a high-end cooled FLIR Phoenix to the more affordable uncooled system Variocam, showed that the uncooled thermal system could compensate for its lower resolution sensitivity via further image processing. Furthermore, the study also showed that the uncooled thermal sensor was still suitable for use in UAVs for navigation applications by analysing SNR data.…”
Section: Thermal Sensor System Considerations For Navigation Applicationsmentioning
confidence: 99%
“…The limitations in available IRT techniques restricted their ability to perform fast and, at the same time, reliable quantitative inspections [30]. The recent development of an advanced variant of IRT, termed Pulsed Phase-informed Lock-in Thermography (PPI-LT), lifted this limitation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Basic CM techniques include vibration analysis (wheels and bearings of the gearbox, generator bearings), oil analysis, thermography and acoustic monitoring (sensors mounted on the turbine equipment) [8]. Nondestructive testing (NDT) is a common way to evaluate the structural integrity of several underground structures [9,10] and aerospace applications [11]. Furthermore, integration of sensors and data mining based technologies has enabled a reliable monitoring process [12].…”
Section: Introductionmentioning
confidence: 99%